2018
DOI: 10.1016/j.rgg.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Rare-metal pegmatoid granites, markers of the beginning of the Hercynian within-plate stage in the Ol’khon region of the Baikal area

Abstract: On the background of Early Paleozoic precollisional, syncollisional, and late collisional igneous rocks prevailing in the region (Khaidai and Shara-Nur granitoids and Birkhin gabbroid complex), rare-metal pegmatoid granite bodies and pegmatites along the southern edge of the Ol’khon region are of particular interest. They have a Middle Paleozoic age (390–391 Ma), cut the Caledonides, and belong to different geochemical types. The Anga unit includes amazonite-containing Li–F–B pegmatites, which are also enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For example, through regional pegmatite, Pedrosa et al [7] studied the opening of the South Atlantic, and Galetskiy [8] and Mints [9] discussed the tectonic evolution of the Eastern Baltic and Ukrainian shields, respectively. Mohammedyasin et al [10] claimed that the rare metal mineralization of the Kenticha deposit in southern Ethiopia marked the end of the East African Orogeny, and Makrygina et al [11] concluded that the Ol'khon rare metal pegmatoid granites marked the beginning of the Hercynian within-plate stage in the eastern Baikal area of Russia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, through regional pegmatite, Pedrosa et al [7] studied the opening of the South Atlantic, and Galetskiy [8] and Mints [9] discussed the tectonic evolution of the Eastern Baltic and Ukrainian shields, respectively. Mohammedyasin et al [10] claimed that the rare metal mineralization of the Kenticha deposit in southern Ethiopia marked the end of the East African Orogeny, and Makrygina et al [11] concluded that the Ol'khon rare metal pegmatoid granites marked the beginning of the Hercynian within-plate stage in the eastern Baikal area of Russia.…”
Section: Introductionmentioning
confidence: 99%